2017
DOI: 10.1155/2017/1318203
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Accuracy of Ultrasound in Assessment of Myometrial Invasion in Endometrial Cancer: Subjective Assessment versus Objective Techniques

Abstract: The aim of this study was to assess the diagnostic accuracy of subjective ultrasound evaluation of myometrial invasion of endometrial cancer and to compare its accuracy to objective methods. All consecutive patients with histologically proven endometrial cancer, who underwent ultrasound evaluation followed by surgical staging between January 2009 and December 2011, were prospectively enrolled. Myometrial invasion was evaluated by subjective assessment using ultrasound (<50% or ≥50%) and calculated as deepest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 37 publications
(41 reference statements)
6
43
0
Order By: Relevance
“…A number of ultrasound studies have been published for the assessment of individual staging parameters to determine the depth of tumor invasion into the myometrium, with ultrasound sensitivity from 61 to 93% and specificity from 71 to 92%, when performed by an expert sonography specialist (2832). The sensitivity reported in the evaluation of tumor invasion in cervical stroma was lower, from 25 to 93%, and specificity from 85 to 99% (30, 33, 34). In a study utilizing expert sonography in a specialized center, Fruhauf et al reported a PPV of 67.6% and NPV of 83.3% for the detection of deep myometrial invasion and PPV of 60.0% and NPV of 88.1% in the detection of tumor affection of the uterine cervix.…”
Section: Discussionmentioning
confidence: 89%
“…A number of ultrasound studies have been published for the assessment of individual staging parameters to determine the depth of tumor invasion into the myometrium, with ultrasound sensitivity from 61 to 93% and specificity from 71 to 92%, when performed by an expert sonography specialist (2832). The sensitivity reported in the evaluation of tumor invasion in cervical stroma was lower, from 25 to 93%, and specificity from 85 to 99% (30, 33, 34). In a study utilizing expert sonography in a specialized center, Fruhauf et al reported a PPV of 67.6% and NPV of 83.3% for the detection of deep myometrial invasion and PPV of 60.0% and NPV of 88.1% in the detection of tumor affection of the uterine cervix.…”
Section: Discussionmentioning
confidence: 89%
“…A recent study analyzing 210 women with proven EC found that both subjective assessment and objective ratios were significant predictors of the myometrial invasion, but subjective assessment was confirmed as the most reliable method to assess myometrial invasion (sensitivity 79% and specificity 73%). 22 A meta-analysis of 35 studies with 6387 women diagnosed of EC found that FSE had a significantly better diagnostic performance than intraoperative gross evaluation (sensitivity 84% vs . 71%) for the intraoperative diagnosis of deep myometrial invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) techniques are highly specific in the assessment of deep myometrial invasion, cervical stromal involvement and lymph node metastasis . The diagnostic performance of TVUS and MRI for detecting myometrial invasion in endometrial carcinoma are quite similar [39,44,56,[83][84][85][86][87][88]. Of note, preoperative ultrasound assessment of deep myometrial and cervical stromal invasion in endometrial carcinoma is best performed by an expert sonographer, as compared to gynecologists, they show a greater degree of agreement with histopathology and greater interobserver reproducibility [84].…”
Section: Pre-and Intra-operative Work-upmentioning
confidence: 98%